The Bubble: A Tool for Mastering Spelling in a Heterogeneous Classroom – A Case Study of Second-Year Middle School Students - GHERBAOUIغرباوي, Amar (El Omda in Linguistics and Discourse Analysis, 2018)
This research aims to show the effect of the bubble as a reliable tool, a didactic device of orthographic control. Thus, the bubble is a powerful instrument of differentiated pedagogy since it can accompany every second year average learner as long as he needs to write his text without making morphosyntactic mistakes. It is then a didactic perspective to know how to practice the bubble to support in an efficient manner the heterogeneity of learners. This disparity of levels is today a delicate adventure, a daily challenge on the part of the teacher, because each student, when he arrives at school, has a particular skill, a singular history and a family adventure that clean. Therefore, to answer our concerns, we formulate the hypothesis that the trajectory of the bubble or bubbles, in the opposite direction of the writing, helps to direct the attention of each student on the links between what he is in writing and what he has already written. The objective of the present study is to bring learners to get closer to this new tool called the bubble and to write without making morphosyntactic errors.